AL-KHAUF DAN AL-RAJA’ MENURUT AL-GHAZALI - M. Ihsan Dacholfany (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
The study form Al-Ghazali abouty Al-Khauf basically urges the people to remember many more about Allah SWT. This also urges to do His order and casts away His prohibitation. But, all of it will not be perfect if it is not run together with the knowledge. It is he explicits that Al-Khauf is a favor of knowledge. With the knowledge, people will consider Allah SWT and love Him and so to the King. It is the hope that is one thing better than feeling scarry. It is because the servants which are closer to Allah SWT, are the servants He loves.